Socioeconomic inequality in intermittent preventive treatment using Sulphadoxine pyrimethamine among pregnant women in Nigeria - Fatima Mahmud Muhammad; Reza Majdzadeh; Saharnaz Nedjat; Haniye Sadat Sajadi; Mahboubeh Parsaeian (BMC, 2020)
Abstract Background Intermittent preventive treatment using Sulphadoxine pyrimethamine (IPTp-SP) for malaria prevention is recommended for all pregnant women in malaria endemic areas. However, there is limited evidence on the level of socioeconomic inequality in IPTp-SP use among pregnant women in Nigeria. Thus, this study aimed to determine the level of socioeconomic inequality in IPTp-SP use among pregnant women in Nigeria and to decompose it into its contributing factors. Methods A secondary data analysis of Nigerian demographic and health survey of 2018 was conducted. A sample of 21,621 pregnant women aged between 15 and 49 years and had live birth in the previous 2 years before the survey were included in this analysis. The study participants were recruited based on a stratified two-stage cluster sampling method. Socioeconomic inequality was decomposed into its contributing factors by concentration index. Result Totally 63.6% of pregnant women took at least one dose of IPTp-SP prophylaxis. Among IPTp-SP users, 35.1% took one dose, 38.6% took two doses and 26.2% took three doses and more. Based on both concentration index of 0.180 (p-value = < 0.001, 95% CI: 0.176 to 0.183) and Erreyger's normalization concentration index 0.280 (p-value = < 0.001, 95% CI: 0.251 to 0.309), the IPTp-SP utilization was pro-rich. The largest contributors to the inequality in IPTp-SP uptake were wealth index (47.81%) and educational status (28.66%). Conclusion Our findings showed that IPTp-SP use was pro-rich in Nigeria. Wealth index and educational status were the factors that significantly contributed to the inequality. The disparities could be reduced through free IPTp service expansion by targeting pregnant women from low socioeconomic status.